Vliv implantace endoprotézy kyčelního nebo kolenního kloubu na medián dožití pacientů starších 80 let - Kubeš, R; Král, A; Stollin, M; Bobelyak, M (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2024)
INTRODUCTION: During the 20th century, the life expectancy increased by 30 years. At the same time, the number of people living longer than that has grown significantly. The aim of this study was to investigate whether total hip or knee arthroplasty (THA or TKA) in patients over 80 years of age does not reduce their life expectancy. MATERIAL AND METHODS: The study examined the data of patients who had undergone THA or TKA between 1994 and 2002 and were older than 80 years at the time of surgery. The study group was divided into a group of patients in whom elective total hip or knee arthroplasty was performed for arthritis and into a group of patients who underwent the same procedure for proximal femur fracture. The investigated parameter was the real survival, which was compared with the life expectancy predicted by the Institute of Health Information and Statistics of the Czech Republic. We also monitored postoperative mortality and postoperative interval after which the life expectancy was no longer reduced. RESULTS: The study included 547 patients. Of whom, 96 patients underwent elective surgery (36%) and 351 patients underwent surgery for intracapsular hip fracture (64%). In the elective surgery group, the survival was longer than the national average: In the 80-84-year group, the median survival was 6.0 years vs. median life expectancy of 5.6 years; in the 85-89-year group, the median survival was 6.3 years vs. median life expectancy of 3.9 years. The fracture surgery group showed a decrease in the life expectancy compared to the national average - in the 80-84-year group, the median survival was 3.5 years vs. median life expectancy of 5.6 years, and in the 85-89-year group, the median survival was 2.9 years vs. median life expectancy of 3.9 years. The likelihood of postoperative mortality was significantly higher in the fracture group than in the elective group (p = 0.05 vs. 0.01), with the difference being the highest in the first 8 weeks after surgery. CONCLUSIONS: Correctly indicated THA or TKA in patients over 80 years of age improves the quality of life of these patients and does not reduce the life expectancy. Intracapsular femoral neck fractures in patients of that age can still be considered as an indication for surgical treatment as a life-saving procedure. KEY WORDS: total hip arthroplasty, total knee arthroplasty, osteoarthritis, hip fracture, life expectancy.
Keywords: Survival Rate; náhrada kyčelního kloubu; míra přežití; lidé; senioři nad 80 let; Arthroplasty, Replacement, Hip; mužské pohlaví; Arthroplasty, Replacement, Knee; Female; Male; naděje dožití; Life Expectancy; Aged, 80 and over; ženské pohlaví; totální endoprotéza kolene; Humans